Essential oil of Lippia alba in the diet of Macrobrachium rosenbergii: Effects on antioxidant enzymes and growth parameters. (18th February 2020) - Cagol, Luana; Baldisserotto, Bernardo; Becker, Alexssandro Geferson; Souza, Carine de Freitas; Heinzmann, Berta Maria; Caron, Braulio Otomar; Leone, Francisco Assis; dos Santos, Lilian Dena; Ballester, Eduardo Luis Cupertino
Abstract: The juveniles of Macrobrachium rosenbergii (0.060 ± 0.004 g and 2.018 ± 0.071 cm) were fed during 60 days with diets containing different doses of Lippia alba essential oil (EOLA) (0.0—control, 1.0, or 2.0 ml EOLA/kg diet; in triplicate, with 20 prawns/replicate). After the experimental period, were verified the survival, growth parameters and the antioxidant enzymes, lipid peroxidation and Na/K‐ATPase activities in hepatopancreas and gills, respectively, of the animals. There were no significant differences on survival, growth parameters and gill Na/K‐ATPase activity. However, glutathione peroxidase and glutathione‐ S ‐transferase activities were lower in hepatopancreas of prawns fed with 1.0 ml EOLA/kg diet compared to the control. Moreover, the activity of the enzyme superoxide dismutase was higher in hepatopancreas of prawns that received 2.0 ml EOLA/kg diet compared to those fed with 1.0 ml EOLA/kg diet. Although the addition of both EOLA doses has not improved the survival and growth parameters of M. rosenbergii, these doses contributed to decrease lipid peroxidation. Additionally, the dose of 2.0 ml EOLA/kg diet contributed for increasing the antioxidant enzymes activities in the hepatopancreas, improving antioxidant status, and therefore, it can be recommended as diet supplementation for M. rosenbergii .